2017
DOI: 10.1039/c7cc07529d
|View full text |Cite
|
Sign up to set email alerts
|

p-Selective (sp2)-C–H functionalization for an acylation/alkylation reaction using organic photoredox catalysis

Abstract: p-Selective (sp)-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
0
22
0
4
Order By: Relevance
“…[199] Upon excitation with visible light, 9,10dimethoxyanthracene induces the generation of alkyl radicals from the corresponding selenides which then add onto various electron-rich unactivated arenes (via the corresponding arene radical cations) used in excess (5 equivalents) to provide the desired alkylated arenes in good yields and with high levels of regioselectivity for the para position. [199] Upon excitation with visible light, 9,10dimethoxyanthracene induces the generation of alkyl radicals from the corresponding selenides which then add onto various electron-rich unactivated arenes (via the corresponding arene radical cations) used in excess (5 equivalents) to provide the desired alkylated arenes in good yields and with high levels of regioselectivity for the para position.…”
Section: Alkylation With Other Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[199] Upon excitation with visible light, 9,10dimethoxyanthracene induces the generation of alkyl radicals from the corresponding selenides which then add onto various electron-rich unactivated arenes (via the corresponding arene radical cations) used in excess (5 equivalents) to provide the desired alkylated arenes in good yields and with high levels of regioselectivity for the para position. [199] Upon excitation with visible light, 9,10dimethoxyanthracene induces the generation of alkyl radicals from the corresponding selenides which then add onto various electron-rich unactivated arenes (via the corresponding arene radical cations) used in excess (5 equivalents) to provide the desired alkylated arenes in good yields and with high levels of regioselectivity for the para position.…”
Section: Alkylation With Other Reagentsmentioning
confidence: 99%
“…In addition to the use of alkenes,alkyl halides,alkylmetal reagents,and cross-dehydrogenative coupling reactions,some transformations have indeed recently been reported for the direct alkylation of unactivated arenes using less conventional alkylating agents:t hese include benzylic alcohols or ethers, aldehydes and ketones, [188] peroxides, [160] diazo compounds, [198] and alkylselenides. [199] In addition to the use of styrenes,Peris also reported that benzylic alcohols or ethers can act as efficient reagents for the direct benzylation of toluene and anisole derivatives in the presence of [IrCp*(OTf) 2 (I nBu )] (Scheme 76). [188] Thes ame catalyst could also promote at andem reaction in which aldehydes and ketones can be utilized as alkylating agents through an in situ reduction to the corresponding alcohols,the actual alkylating agents.Overall, the desired alkylated arenes are obtained in good yields and moderate to good ortho/para selectivities.…”
Section: Alkylation With Other Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the use of alkenes, alkyl halides, alkylmetal reagents, and cross‐dehydrogenative coupling reactions, some transformations have indeed recently been reported for the direct alkylation of unactivated arenes using less conventional alkylating agents: these include benzylic alcohols or ethers, aldehydes and ketones, peroxides, diazo compounds, and alkylselenides …”
Section: Alkylation Of Simple Arenesmentioning
confidence: 99%
“…Finally, Pandey reported the para ‐selective alkylation of simple arenes with alkylselenides using photoredox catalysis (Scheme ) . Upon excitation with visible light, 9,10‐dimethoxyanthracene induces the generation of alkyl radicals from the corresponding selenides which then add onto various electron‐rich unactivated arenes (via the corresponding arene radical cations) used in excess (5 equivalents) to provide the desired alkylated arenes in good yields and with high levels of regioselectivity for the para position.…”
Section: Alkylation Of Simple Arenesmentioning
confidence: 99%